Assessment of Preventive Behaviors of Head Lice Infestation Based on Health Belief Model in Female College Students - Vahid Kohpeima Jahromi; Razieh Zahedi; Zeinab Balaghi; Sara Mardaneh; Nader Sharifi (Shahid Sadoughi University of Medical Sciences, 2023)
Background: People's health behaviors are important in determining the prevalence of the head lice infestation. This study aimed to determine the preventive behaviors of head lice infestation using the Health Belief Model (HBM) in female students of Jahrom University of Medical Sciences. Methods: This cross-sectional study was conducted on 255 female students of Jahrom University of Medical Sciences, Fars Province, South of Iran in 2021. Sampling was randomly selected from female students studying in the fields of public health, operating room, anesthesia, nursing, laboratory sciences, and medicine. The data collection tool was a four-part standard "preventive behaviors against pediculosis infection" questionnaire whose validity and reliability have been confirmed. The questionnaire was completed by the participants and the data were entered into SPSS 21 for analysis. Data analysis was performed descriptively with the report of frequency, percentage, mean and standard deviation. The correlation was evaluated using Pearson correlation test. Significance level was considered less than 0.05. Results: The mean age and number of roommates (SD) of the participants were 22.4 (1.7) and 3.35 (1.3), respectively. There was a positive and significant correlation between the perceived benefits construct and knowledge (r = 0.147, p = 0.04) and the perceived susceptibility construct (r = 0.413, p < 0.001). In addition, a positive and significant correlation was observed between the behavior with knowledge (r = 0.144, p = 0.04) and self-efficacy construct (r = 0.167, p = 0.02). There was a significant inverse correlation between perceived barriers construct with knowledge (r = -0.265, p < 0.001) and behavior (r = -0.213, p = 0.002), as well as between self-efficacy construct and knowledge (r = -0.219, p = 0.001). Conclusion: To improve preventive behaviors of lice infestation in students, in addition to improving people's knowledge, efforts should be made to identify and remove barriers to healthy behavior as well as improve people's perception of these barriers. Corresponding Author: Nader Sharifi View Orcid in Profile You can search for this author in PubMed & Google Scholar Profile